Neuro-fuzzy Hybrid System for Monitoring Wood Moisture Content During Drying - Antônio José Vinha Zanuncio; Amélia Guimarães Carvalho; Carlos Alberto Araújo Júnior; Maíra Reis de Assis; Liniker Fernandes da Silva (Floresta e Ambiente, 2019)
ABSTRACT The heterogeneous behavior of wood during drying is a process difficult to control. The objective of this study was to evaluate the accuracy of the neuro-fuzzy hybrid system for monitoring wood moisture during drying. Eucalyptus urophylla x Eucalyptus grandis samples (2 x 2 x 4 cm) were saturated and dried in climatic chamber for 15 days. Basic density was determined by the dry mass/saturated volume ratio. Two neuro-fuzzy systems were developed to monitor wood moisture, the first based on the genetic material and drying period and the second based on basic density and drying period. The drying rate of wood samples was higher at the initial period and all reached equilibrium moisture content after 15 days. Density showed relationship with wood moisture during the study period. Both systems have the potential to monitor moisture, however, neuro-fuzzy system based on basic density and drying period showed better results and is therefore more suitable.